Nano-Synthetic Devices in Leishmaniasis: A Bioinformatics Approach - Mol, Milsee; Kosey, Dipali; Singh, Shailza (Frontiers in Immunology, 2015)
Synthetic biology is an investigative and constructive means of understanding the complexities of biology. Substantial progress in the field has resulted in the creation of synthetic gene circuits which when uploaded into the appropriate nanoliposomal vehicle, can be used for a tunable response in a cell. These tunable elements can be applied to treat diseased conditions for a transition to a healthy state. Though in its nascent stage of development synthetic biology is beginning to use its constructs to bring engineering approaches into biomedicine for treatment of infectious diseases.